INCREASING VOCABULARY OF THE EIGHTH GRADE STUDENTS OF SMP NEGERI 2 PALU THROUGH THE USE OF TIKTOK - Septiani, Cindy; Darmawan, Darmawan; Budi, Budi; Marhum, Mochtar (e-Journal of ELTS (English Language Teaching Society), 2025)
The objective of this research is to find out if the use of TikTok as a learning media can increase students’ vocabulary of SMP Negeri 2 Palu. This research used a quasi-experimental design that consisted of two classes; experimental and control class. The samples of this research was the second grade students of SMP Negeri 2 Palu; VIII Pangeran Diponegoro (class B) with 31 students as the experimental class and VIII Kapitan Pattimura (class E) with 32 students as the control class that was selected by using cluster random sampling. The data was collected by administering a vocabulary test consisting of a pre-test and post-test that was conducted at first and last meetings. Then the treatment was only given to the experimental class. The result of the experimental class’s pre-test is 45.38, while the control class is 51.04. The result of the experimental class’s post-test is 70.00, while the control class is 62.29. By applying 0.05 level of significance, the researchers found that the value of the t-counted (7.15) is higher than the t-table (1.671). It can be concluded that the use of TikTok as learning media in teaching vocabulary is effective to increase students’ vocabulary of SMP Negeri 2 Palu. Based on these results, it implies that TikTok can be applied by teachers in the teaching and learning process as one of effective media to increase students' vocabulary, especially for second grade students of junior high school.